2005
DOI: 10.1128/iai.73.11.7107-7112.2005
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Tight Junctions during Traversal of the Respiratory Epithelium by Burkholderia cenocepacia

Abstract: Burkholderia cenocepacia is an opportunistic bacterial species capable of causing life-threatening respiratory tract infection in persons with cystic fibrosis (CF). Unlike most other pathogens in CF, which typically remain confined to the endobronchial spaces, B. cenocepacia can traverse airway epithelium to cause bacteremia and sepsis. The mechanisms by which this occurs, however, are unknown. We examined the transmigration of B. cenocepacia through polarized respiratory epithelium. Representatives of three "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 37 publications
2
45
1
Order By: Relevance
“…It was also suggested that the ability of H. influenzae to penetrate the epithelial layer protects them from antibiotics and antibody-mediated bactericidal activity (25). Burkholderia cenocepacia also disrupts a differentiated epithelial barrier, an event associated with loss of occludin from tight junctions (26).…”
Section: Discussionmentioning
confidence: 99%
“…It was also suggested that the ability of H. influenzae to penetrate the epithelial layer protects them from antibiotics and antibody-mediated bactericidal activity (25). Burkholderia cenocepacia also disrupts a differentiated epithelial barrier, an event associated with loss of occludin from tight junctions (26).…”
Section: Discussionmentioning
confidence: 99%
“…After 90 min of incubation, infection medium from the apical surface was replaced with fresh growth medium, and the cells were further incubated for 4 to 24 h at 33°C. In inhibition studies, N-propyl gallate, diphenylene iodonium (DPI), oxypurinol, quercetin (all from SigmaAldrich, St. Louis, MO), or the Rac1 inhibitor NSC23766 (EMD Chemicals, Gibbstown, NJ) was added to both the apical and basolateral chambers 90 min after RV infection and incubated for 24 h, and R T was measured with an Evom voltmeter equipped with an EndOhm 6 tissue resistance measurement chamber (World Precision Instruments, Sarasota, FL) (25,41).…”
Section: Methodsmentioning
confidence: 99%
“…After coating, Transwells and coverslips were washed twice with phosphate-buffered saline (PBS) and RPE cells were seeded at 2 ϫ 10 5 /ml in DMEM/F12 supplemented with 5% FBS and 1% GLN. Medium was removed from the apical chamber at 48 to 72 h postseeding to create an air-liquid interface and to stimulate polarization (day 0) (33). Polarized monolayers were incubated for 15 days before infection.…”
Section: Methodsmentioning
confidence: 99%